Extremum seeking control for maximum power point tracking of PV systems - BAOUCHI Slimane; Hamama Aicha; BENMOUIZA Khalil (Université Amar Thelidji- Laghouat.FACULTE : TECHNOLOGIE.DEPARTEMENT : ELECTROTECHNIQUE, 2021)
Photovoltaic systems are used widely nowadays as alternative source for generating electricity. They are composed of Solar panels, battery, converters, inverters and maximum power point tracker MPPT solar charge controller. MPPT are the elements of an installation that give real energy freedom. They are also major marketing arguments for a business today. The MPPT regulator optimizes the operation of an autonomous electrical system. So, this is a way to increase energy savings. The MPPT regulator scans the electrical voltage produced by the photovoltaic panel several times a day. Its purpose is to find the maximum output point of the current supplied by the panel. Then make sure to always use this full power. In short, the MPPT charge controller derives maximum power from the panel. It makes an installation intelligent. Several methods are proposed to reach this maximum power point such as perturb and observe, hill climbing, artificial intelligence and others. However, they always suffer from drawbacks especially in the case of cloudy days. Hence, we propose in this work an extremum seeking control (ESC) in order to track the maximum power generated from a photovoltaic system. ESC is a kind of adaptive control which can drive and maintain the input and output ofthe controlled object to their respective extrema. A full simulation in Matlab of a PV system controlled by ESC will be given in detailed and simulation results will be discussed.
Option : Automatic